Hukum Penggunaan Vaksin Astrazeneca (Analisis Fatwa MUI No. 14 Tahun 2021) - Melia - Rosa (Jurnal AL-AHKAM, 2023)
This paper examines the legal status of the use of the Astrazeneka vaccine, which is indicated to utilize pork trypsin media which has caused controversy in the community. The polemic surfaced after a different fatwa was issued between the Central MUI which forbade it and the East Java MUI which made the Astrazeneka vaccine legal. This paper provides an explanation of the halalness of the astrazeneca vaccine by applying the theory of istihalah, after going through a long production process there have been changes both in substance and form so that the nomenclature has also changed, the astrazeneka vaccine which uses pork trypsin is considered holy and halal. Halal law is based on the argument that the illat of law that causes prohibition has disappeared.